The marketization of social security - Dixon, John E., 1946 May 9-; Hyde, Mark, 1958- (Quorum Books, 2001)
Annotation Much could be gained from the privatization of social security--but can the gains actually be delivered? Dixon, Hyde, and their contributing authors take a balanced look at where we are now, and where we seem to be moving, on the issues of social security privatization and come up skeptical. There will be tradeoffs, but will the benefits outweigh the costs? Their volume examines a variety of settings in Latin America, Asia, Europe, North America, and Africa, where the "marketization" of social security appears most hotly contested. As a contribution to this new, energetic gobal policy discourse, the book will be of special interest to policymakers in the public and private sectors, and particularly in organizations where concerns about the growing cost of employee benefits have become critical. Dixon, Hyde, and the others start by showing how the concept of social security has changed dramatically over the last 20 years--not just in the United States but throughout the world. The collectivist ideology that has long underpinned social security policy has been challenged by the emergence of an ideology of individualism. But can one presume that the desires of government to privatize are driven purely by the need to achieve neoliberal policy goals by that means? Too simplistic, say the contributors. Marketization offers the promise of reduced dependency on the state, reduced public expenditure and thus lower taxes, enhanced competitiveness internationally, more efficient delivery of social security services, and other advantages--but whether these promises would be kept seems to depend on a variety of factors. Among them, explored in this volume, are the level of development and sophistication of the capital markets, the degree of market competition that can be achieved and sustained, and the capacity of the state to develop and implement governance mechanisms to ensure that private providers act in the public interest. The volume also examines two daunting challenges to governments: how to design a set of regulations that can protect the public interest in perpetuity, and how to resist the calls for government subsidies to support the economic rent expectations of privatized providers. The contributors and editors develop these and other points concisely and readably, and in doing so offer important lessons from the experiences of others worldwide